Pengaruh Penambahan Tepung Sinbiotik Dari Kulit Nanas Dan Inulin Bengkuang Terhadap Berat Relatif Organ Limfoid Ayam Broiler: The Effect of Adding Synbiotic Flour From Pineapple Peel and Jicama Inulin on the Relative Weight of Broiler Chicken Lymphoid Organs - Fauzi, Ahmad; Rinawidiastuti, Rinawidiastuti; Iskandar, Faruq (Universitas Muhammadiyah Purworejo, 2025)
This study aimed to determine the effect of adding synbiotic flour from pineapple peel (Ananas comosus) and jicama inulin (Pachyrhizus erosus) on the relative weight of lymphoid organs (thymus, bursa of Fabricius, and spleen) in broiler chickens. A total of 100 female DOC broilers were used in a Completely Randomized Design (CRD) with 5 treatments and 4 replicates, where each replicate consisted of 5 chickens. The treatments involved supplementing synbiotic flour at doses of 0% (P0, control), 5% (P1), 10% (P2), 15% (P3), and 20% (P4) of the total commercial feed weight. Data were analyzed using Analysis of Variance (ANOVA) followed by Duncan's Multiple Range Test (DMRT) at a 5% significance level. The results showed that the addition of synbiotic flour had a significant effect (P<0.05) on the relative weight of the broiler chicken thymus. Treatment P3 (15% synbiotic) resulted in the highest thymus weight with a mean of 0.61±0.01%, which was within the normal range (0.30% - 0.60%) and indicated an optimal immunostimulant effect. Conversely, treatment P4 (20% synbiotic) showed the lowest thymus weight (0.33±0.10%), suggesting a potential decrease in immune response or mild toxic effects due to excessive dosage. Treatments P0, P1, and P2 showed relatively similar mean thymus weights and did not differ significantly compared to the control. However, the addition of synbiotic flour did not have a significant effect (P>0.05) on the relative weight of the bursa of Fabricius and spleen in broiler chickens at all treatment levels. The relative weights of the bursa of Fabricius and spleen in all treatment groups remained within the normal range (0.07% - 0.11% for bursa of Fabricius and 0.12% - 0.15% for spleen). Addition of synbiotic flour from pineapple peel and jicama inulin has the potential to strengthen the immune system of broiler chickens, particularly through increased thymus development at a 15% dose.